Optothermal Raman Spectroscopy for Thermal Transport Study - Gupta J.D.; Jangra P.; Mishra A.K. (My University, 2025)
Experimentally thermal transport properties of nanomaterials can be studied by two ways: steady-state and transient measurements. The suspended thermal bridge, electron beam self-heating method, and Raman methods are the prime examples of steady state measurements, while 3ω method, time-domain thermoreflectance method (TDTR), and Laser-flash technique (LFT) measurement are the key methods for transient study. The optothermal Raman technique method is one of the best experimental techniques to study the thermal conductivity of two dimensional (2D) materials like Graphene, transition metal dichalcogenides (TMDCs), boron nitride (BN), black phosphorous (bPh), etc. using appropriate heat conduction model. This technique is also useful for analysing the fundamental phonon scattering mechanisms through analysis of the temperature-dependent mode shift carried by phonon anharmonicity and thermal expansion in low dimensional materials. This chapter provides a glimpse of different methods for thermal transport studies in nanomaterials. We discuss the optothermal Raman technique in detail for extracting thermal conductivity and observing linear/non-linear thermal transport responses of low dimensional materials. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.